PENGARUH RETURN ON ASSETS, NET PROFIT MARGIN DAN EARNING PER SHARE TERHADAP RETURN SAHAM PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK - Selviani, Novita; Putra Prima, Argo (EDUTECH CONSULTANT, 2020)
In Indonesia the capital market has increased share sales. Before buying shares, investors should analyze their reports using financial ratios, the ratios used in this study are Return On Assets, Net Profit Margin and Earning Per Share. The purpose of this study was to determine the effect of ROA, NPM and EPS on the stock returns of Consumer Goods Industry companies listed on the Indonesia Stock Exchange in the period 2014 - 2018. Sampling of 22 companies using purposive sampling and this research is a quantitative study using multiple linear regression analysis. From the results of the analysis of the T ROA test has a significant level of 0.634> 0.05, NPM has a significant level of 0.792> 0.05 and EPS has a significant level of 0.037 <0.05. This explains partially ROA and NPM have no effect on stock returns and only EPS has a significant effect and positive on stock returns. From the results of the analysis of the F ROA test, NPM and EPS have a significant level of 0.033 <0.05 which explains simultaneously have a significant and positive effect on stock returns.